Health experiences of asylum seekers and refugees in Wales. (13th November 2019) - Scott, R; Ellis, L; Khanom, A; Rhydderch, M; Richardson, G; Russell, D; Russell, I; Snooks, H
Abstract: : There are concerns that people seeking sanctuary (asylum seekers and refugees) in Wales, UK, have unmet health needs and face difficulties accessing services, but little collated evidence. This study addressed this gap to inform policy and practice in reducing health inequities. It aimed to: investigate the health, wellbeing and healthcare experiences of adults seeking sanctuary in Wales, including the views of healthcare recipients and providers; and establish what helped or hindered the healthcare experiences of those seeking sanctuary. It is the most comprehensive study of this population in Wales. A mixed-method approach was taken, including a literature search, a cross-sectional survey of 210 adults seeking sanctuary, telephone interviews with 32 health professionals and third sector support workers, and 8 focus groups including 57 people seeking sanctuary and those supporting them. Eight trained volunteer peer researchers, themselves asylum seekers or refugees, administered the surveys. Interviews were digitally recorded, transcribed and analysed using a standard framework. The literature search identified 5 themes that help or hinder people seeking sanctuary to access healthcare. The survey found 79% of respondents attended an initial health assessment on arriving in Wales, with 94% currently registered with Primary healthcare. 64% reported difficulties in accessing health services. Awareness of services was mixed, with 66% having used healthcare in working hours (planned) and 28% out of hours (unplanned). Mainstream health professionals felt they lack capacity to deliver care effectively due to time and other pressures on the healthcare system and the need for appropriate translation/interpretation services. This study triangulates the experiences of people seeking sanctuary with those providing healthcare and general support. Peer researchers maximised sanctuary seekers' participation. Many of its methods and findings have relevance to other countries in Europe. Key messages: Improving health equity is key to realising Wales' ambition to become a Nation of Sanctuary. Peer Researchers enabled participation by sanctuary seekers and revealed useful findings to steer future policy and practice.